2010
DOI: 10.1002/adma.201001006
|View full text |Cite
|
Sign up to set email alerts
|

Dye‐Sensitized Back‐Contact Solar Cells

Abstract: Dye‐sensitized back‐contact solar cells are fabricated on back plates comprising a patterned FTO glass substrate, a selectively deposited Pt coating, a protective ZrO2 coating covering the Pt layers and a screen printed TiO2 film. Such devices show a solar energy conversion efficiency of 3.64% under AM 1.5 sunlight and a peak incident photon to electron conversion efficiency of 54%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…[3,4] Generally, improvements in overall PCE have focused on increasing the photovoltage through the modification of the oxide layer, improving the photocurrent with new dye molecules, and increasing the stability by controlling the cell configurations. [4,5] A transparent mesoporous TiO 2 nanoparticulate layer is a well-known photoanode material used in conventional DSSCs. However, the small size of TiO 2 nanoparticles (diameter ∼ 20 nm) makes this layer transparent to visible light, and thus weakly light scattering due to the small particle size.…”
Section: Doi: 101002/adma201103985mentioning
confidence: 99%
“…[3,4] Generally, improvements in overall PCE have focused on increasing the photovoltage through the modification of the oxide layer, improving the photocurrent with new dye molecules, and increasing the stability by controlling the cell configurations. [4,5] A transparent mesoporous TiO 2 nanoparticulate layer is a well-known photoanode material used in conventional DSSCs. However, the small size of TiO 2 nanoparticles (diameter ∼ 20 nm) makes this layer transparent to visible light, and thus weakly light scattering due to the small particle size.…”
Section: Doi: 101002/adma201103985mentioning
confidence: 99%
“…As shown in the experiments, the power conversion efficiencies were only 1.95 % [7] and 5.77 % [11] with the plasmonic effect considered. We show in next section that the parasitic absorption of small metal nanoparticles is the main reason, and the power conversion efficiency enhanced by metallic nanoparticles is much less than their enhanced efficiency of light collection because the metallic nanoparticles absorb one part of the incident light during surface plasmon resonance (SPR).…”
Section: Introductionmentioning
confidence: 98%
“…Fu et al [11] reported the conversion efficiency of the typical DSSC with the Pt fishnet arrays as the counter electrode, Durr et al [12] studied the effect of the Ag thin-film on the short circuit current in DSSC with a planar waveguide structure.…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, Fu et al [7] reported the fabrication process of a monolithic, back-contact, dye-sensitized solar cell (BC-DSC) with an array of two interdigitated finger electrodes. Both the working and counter electrodes were placed onto the same substrate to efficiently extract photogenerated positive and negative charges from an overlying dye-sensitized heterojunction (Fig.…”
Section: Introductionmentioning
confidence: 99%